Problem-based learning containing local potential to increase junior high school students' interest in biodiversity topic - Murti, Adek Diah; Winarno, Nanang; Kurniasih, Encih; Samsudin, Achmad (Inornatus: Biology Education Journal, 2024)
One of the criteria for good learning is learning that can give rise to positive student responses. The purpose of this study is to assess whether adopting problem-based learning with local potential in biodiversity materials increases students' motivation to learn. The research approach employed was a pre-experimental design with one group pretest-posttest. The population in this research was seventh-grade students, with a research sample of one class and a total of 33 students determined based on convenience sampling. The data collection instrument used the ARCS system learning interest questionnaire (Attention, Relevance, Confidence, Satisfaction) developed by Keller (2000). The test result data was processed using the N-gain test and the Wilcoxon test. The results of the research show that students' overall interest in learning has increased by 0.34 in the medium category. The Wilcoxon test yielded a significance value of 0.00 <0.05, rejecting H0 and accepting Ha. Based on these findings, we may infer that the problem-based learning model with local potential is beneficial in enhancing students' interest in learning about biodiversity.